Studies on Length-Weight Relationship of a Hill-Stream Loach, Schistura cupicola (McClelland) - Ansumal, Aman; Subba, Bharat Raj (Journal of Natural History Museum, 2009)
The study of length-weight relationship of a hill-stream loach, Schistura rupicola McClelland collected from Lampengwa Khola, Nepal was done using the least square formula W=aLTb. The values of ’a’ and ’b’ calculated from the measurement of total length and total body weight were -2.1431 and 3.0508 respectively. The computed value of correlation coefficient (r) was 0.9970. Key words: Correlation coefficient; Regression coefficient; Allometric growth; Body weight. Journal of Natural History Museum Vol. 24, 2009 Page : 126-129